Speed control of sensorless rotor field oriented for faulty three-phase induction motor by using extended kalman filter [electronic resource] - Monadi, Ali, 1985- (2013)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - UniversitiTeknologi Malaysia, 2013